Mechanistic understanding of metabolic cross-talk between Aloe vera and native soil bacteria for growth promotion and secondary metabolites accumulation - Chandel, Neha Singh; Singh, H. B.; Vaishnav, Anukool (Frontiers in Plant Science, 2025)
Plants release a wealth of metabolites into the rhizosphere that can influence the composition and activity of microbial communities. These communities, in turn, can affect the growth and metabolism of the host plant. The connection between medicinal plant and its associated microbes has been suggested, yet the mechanisms underlying selection of indigenous microbes, and their biological function in medicinal plants are largely unknown. In this study, we investigated how the Aloe vera plants select its rhizosphere bacteria and examined their functional roles in relation to plant benefit. We utilized two native plant growth promoting rhizobacterial (PGPR) strains of Aloe vera: Paenibacillus sp. GLAU-BT2 and Arthrobacter sp. GLAU-BT16, as either single or consortium inoculants for plant growth experiment. We analyzed non-targeted root metabolites in the presence of both single and consortium bacterial inoculants and confirmed their exudation in the rhizosphere. The GC-MS analysis of metabolites revealed that the bacterial inoculation in Aloe vera plants amplified the abundance of flavonoids, terpenes and glucoside metabolites in the roots, which also exuded into the rhizosphere. Flavonoids were the most common prevalent metabolite group in individual and consortium inoculants, highlighting their role as key metabolites in interactions with rhizosphere microbes. In addition, the bacterial inoculants significantly increased antioxidant activity as well as total phenolic and flavonoid content in the leaves of Aloe vera. In conclusion, we propose a model of circular metabolic communication in which rhizosphere bacteria induce the production of flavonoids in plants. In turn, the plant releases some of these flavonoids into the rhizosphere to support the indigenous microbial community for its own benefit.